Association of Higher CD4+CD25highCD127low, FoxP3+, and IL‐2+ T Cell Frequencies Early After Lung Transplantation With Less Chronic Lung Allograft Dysfunction at Two Years. Issue 6 (24th January 2017) - Salman, J.; Ius, F.; Knoefel, A.‐K.; Sommer, W.; Siemeni, T.; Kuehn, C.; Tudorache, I.; Avsar, M.; Nakagiri, T.; Preissler, G.; Hatz, R.; Greer, M.; et al.
Abstract : Regulatory T cells (Treg) can regulate alloantigens and may counteract chronic lung allograft dysfunction (CLAD) in lung transplantation. We analyzed Treg in peripheral blood prospectively and correlated percentages of subpopulations with the incidence of CLAD at 2 years. Among lung‐transplanted patients between January 2009 and July 2011, only patients with sufficient Treg measurements were included into the study. Tregs were measured immediately before lung transplantation, at 3 weeks and 3, 6, 12, and 24 months after transplantation and were defined as CD4 + CD25 high T cells and further analyzed for CTLA4, CD127, FoxP3, and IL‐2 expressions. Between January 2009 and July 2011, 264 patients were transplanted at our institution. Among the 138 (52%) patients included into the study, 31 (22%) developed CLAD within 2 years after transplantation. As soon as 3 weeks after lung transplantation, a statistically significant positive association was detected between Treg frequencies and later absence of CLAD. At the multivariate analysis, increasing frequencies of CD4 + CD25 high CD127 low, CD4 + CD25 high FoxP3 + and CD4 + CD25 high IL‐2 + T cells at 3 weeks after lung transplantation emerged as protective factors against development of CLAD at 2 years. In conclusion, higher frequencies of specific Treg subpopulations early after lung transplantation are protective against CLAD development. Abstract : Salman and colleagues explore the relationship between the frequencies of T regulatory cell subpopulations and the development of chronic lung allograft dysfunction after lung transplantation and demonstrate an association between higher CD4 + CD25 high CD127 low, FoxP3 +, and IL‐2 + T cell frequencies early after lung transplantation and less chronic lung allograft dysfunction at two years.